2023
DOI: 10.1007/s10067-023-06500-3
|View full text |Cite|
|
Sign up to set email alerts
|

An online survey of the Spanish Lupus Patient Association (FELUPUS): patient perceptions and experiences

Abstract: Objectives A survey conducted by the Spanish Lupus Federation (FELUPUS) shows the results on perceptions and experiences of the people who live with lupus in Spain. The information was gathered anonymously from May 21 st to June 30 th , 2020. The aim of the study was to monitor the impact of the disease on quality of life, as well as to measure the impact of organ damage in lupus patients. Methods A national survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…An online survey of the Spanish Lupus Patient Association (FELUPUS) reported that 73% of Spanish SLE patients perceived a lack of knowledge about the disease at the time of diagnosis, with 92% of patients having a low level of SLE knowledge. 12 Similarly, a study analyzed SLE patients' knowledge and health-related quality of life found very low baseline levels of SLE knowledge among Iranian SLE patients, with a significant impact on patients' health-related 944 quality of life. 13 A recent qualitative investigation has highlighted the inadequate provision of clear and consistent information to patients with SLE at the time of diagnosis, leading to further distress and confusion among this population.…”
Section: Discussionmentioning
confidence: 99%
“…An online survey of the Spanish Lupus Patient Association (FELUPUS) reported that 73% of Spanish SLE patients perceived a lack of knowledge about the disease at the time of diagnosis, with 92% of patients having a low level of SLE knowledge. 12 Similarly, a study analyzed SLE patients' knowledge and health-related quality of life found very low baseline levels of SLE knowledge among Iranian SLE patients, with a significant impact on patients' health-related 944 quality of life. 13 A recent qualitative investigation has highlighted the inadequate provision of clear and consistent information to patients with SLE at the time of diagnosis, leading to further distress and confusion among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Employment status 31 is another factor impacting QOL, as working late shifts may similarly affect overall well-being. 32 Among the reasons for SLE patient visits, those with relapses exhibited lower QOL scores. 33 This could be linked to the fear and uneasiness individuals experience during relapses, as well as challenges in maintaining consistent medication.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been shown that a lack of knowledge about the disease has negative implications for patients and the healthcare system, worsening prognosis, negatively impacting QoL, and increasing healthcare utilization. 1,[6][7][8] The aim of this paper is to draw attention, according to the perspective of the participants of this study, to the lack of awareness of SLE and its consequences in Spain, and to suggest improvements. Firstly, we focus on the lack of disease awareness by HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of knowledge about SLE, affecting the general population and health care professionals (HCPs) alike. 1 3 The frequently non-specific symptoms of the disease’s onset make its early diagnosis difficult. 4 Furthermore, the “invisibility” of some of SLE’s symptomatology contributes to the lack of understanding by the patients’ social circle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation